Dietary Iron Intake in Pregnant Women in Europe: A Review of 24 Studies from 14 Countries in the Period 1991–2014 - Nils Thorm Milman (Journal of Nutrition and Metabolism)
Objective. Assessment of dietary iron intake in pregnant women in Europe. Design. Review. Setting. Literature search of dietary surveys reporting the intake of dietary iron using the PubMed and Google Scholar databases covering the years 1990–2019. Subjects. Healthy pregnant women. Results. 24 dietary surveys/studies in 14 European countries were included. Nine studies (38%) used Food Frequency Questionnaires, which yielded significantly higher iron intake than studies using Dietary Records. Results from Dietary Record studies in 11 countries showed that iron intake varied between 8.3–15.4 mg/day with an estimated “median” value of 10–11 mg/day. Spain, Bosnia, and Poland reported an intake of 8.3–10.1 mg/day, Croatia, England, Norway, and Finland an intake of 10.2–11.4 mg/day, and Germany, Portugal, Czech Republic, and Greece an intake of 12.2–15.4 mg/day. The recommended iron intake in the various countries varied from 14.8–30 mg/day. In all studies, 60–100% of the women had a dietary iron intake below the recommended intake. Conclusions. In Europe, the majority of pregnant women have a dietary iron intake, which is markedly below the recommended intake. This contributes to a low iron status in many pregnant women. Most guidelines do not advice routine iron supplements, while two guidelines (World Health Organization and Nordic Nutrition Recommendations) recommend routine iron supplementation during pregnancy. Within the European community, we need to reach consensus on the various guidelines and on the issue of iron supplementation. We should establish common European standardized dietary methods, uniform Dietary Reference Values, and uniform statistical methods in order to perform more reliable comparisons between studies in different countries.